Ніке – Вікторія: сцени жертвоприношення тварин на монетах Давньої Еллади і Риму - Русяєва, М.; Rusyaeva, M. (ЦНТУ, 2025)
У статті проаналізовано рідкісні іконографічні типи зображень богині перемоги — Ніке у нумізматиці Стародавньої Еллади та Вікторії у монетному мистецтві Стародавнього Риму, зокрема сцени жертвоприношення барана й бика. Встановлено їхній зв’язок із класичним мистецтвом Афін, впливом храмового рельєфу Храму Афіни-Ніке та військово-політичним контекстом епохи. The article analyzes rare iconographic types of images of the goddess of victory - Nike in the numismatics of Ancient Greece and Victoria in the coinage of Ancient Rome, in particular scenes of the sacrifice of a ram and a bull. Their connection with the classical art of Athens, the influence of the temple relief of the Temple of Athena-Nike, and the military-political context of the era are established.
Nike – Victoria: scenes of animal sacrifice on coins of Ancient Greece and Rome
Keywords: Ніке; Вікторія; антична нумізматика; іконографія жертвоприношення; Nike; Victoria; ancient numismatics; iconography of sacrifice